Proposed Brand Awareness Increase on Buying Interest at Sumiko Coffee Shop - Antonius Hanafi, Eric; Sukapto, Paulus (Ann Publisher, 2024)
In Bandung, coffee has grown to be a way of life and is highly valued. Nestled in Pasir Kaliki Square, specifically on Pasir Kaliki Street, is the Bandung-born coffee shop known as Sumiko. Based on 20 interviews, it is known that 80% of people need to be made aware of Sumiko Coffee Shop; as a result, sales from January 2022 to December 2022 fell short of the objective. Low awareness is the reason behind the need for more sales. In order to raise brand recognition, efforts must be made. First, based on interviews and literature reviews, identify the elements that affect brand awareness—such as advertising, social media marketing campaigns, and word-of-mouth—in the following stages. Distributing questionnaires was the method used to collect data. SmartPLS4 software was then used to process the data from the questionnaire. According to the data processing results, advertising and word-of-mouth factors considerably impact brand awareness. Giving out flyers, making promotional boards, showcasing the uniqueness of the product, allowing reviews and comments, and setting up promotions where customers who bring in a certain number of friends receive a discount or other incentives are some examples of proposals that can be made.